Hasan Çayı (Erzin-Hatay) Su Kalitesi Özellikleri ve Aylık Değişimleri - Mutlu, Ekrem; Tepe, Yalçın; Alpaslan, Ateş; Töre, Yalçın (Ege Ü. Su Ürünleri Dergisi 2006 E.U. Journal of Fisheries & Aquatic Sciences 2006 Cilt/Volume 23, Ek/Suppl. (1/1): 149-154, 2006)
Abstract: Water quality of Hasan stream (Erzin-Hatay) and its montly variations. In the present study, some water quality parameters of Hasan Creek, which source from city of Osmaniye, flow through dense woody area and merge into İskenderun Bay from Dörtyol, Hatay, were investigated. The creek supplies the drinking water of Dörtyol and Payas towns. Starting from May 2003 and sampling the water monthly for a year, water quality parameters of pH, dissolved oxygen, temperature, salinity, Chemical Oxygen Demand (COD), total alkalinity and hardness, ammonia, nitrite, nitrate, phosphate, sulphite, sulphate, chloride, potassium, sodium, silica and total dissolved solids were measured in the present study. According to measured study results, changes in water quality parameters of Hasan Creek respect to the months were determined. Measured water quality parameters indicated that the creek water is suitable for the culture of cold-water fish such as trout. Bu çalışmada, kaynağı Osmaniye ili sınırları içerisinde olan ve sık ormanlık alandan geçerek Hatay ili Dörtyol ilçesinde İskenderun körfezine dökülen Dörtyol ve Payas ilçelerinin içme suyunu karşılayan Hasan Çayı’nın bazı su kalitesi özelliklerinin belirlenmesi amaçlanmıştır. Çalışmaya Mayıs 2003’te başlanmış olup su kalitesi parametrelerinden pH, çözünmüş oksijen, sıcaklık, tuzluluk, kimyasal oksijen ihtiyacı (KOİ), toplam alkalinite ve sertlik, amonyak, nitrit, nitrat, fosfat, sülfit, sülfat, klor, potasyum, sodyum, silisyum ve askıda katı madde (AKM) değerleri 12 ay boyunca aylık olarak incelenmiştir. Yapılan çalışma sonucunda Hasan Çayı su kalitesi parametrelerinin aylara göre değişimleri belirlenmiş olup ayrıca mevcut su kalitesi durumu alabalık gibi soğuk su türlerinin yetiştiriciliği için uygun olduğu görülmüştür.
Keywords: Su kalitesi, Hasan Çayı, Dörtyol, Hatay.; Water Quality, Hasan Creek, Dörtyol, Hatay.